Pelatihan Pembuatan Sabun Kopi dan Edukasi Cuci Tangan untuk Menekan Penularan Penyakit di Sekolah Dasar - Wibawa, Agung Ari Chandra; Adrianta, Ketut Agus; Sari, Ni Wayan Suryani Puspita (Jurnal Pengabdian UNDIKMA, 2024)
The service activity aims to increase students' knowledge and skills in processing natural coffee ingredients into soap to prevent disease transmission in the school environment. The method of implementing this service used training and education. This service partner was SD Negeri 5 Subagan, Karangasem District, Karangasem Regency, Bali Province. The evaluation instruments used in this service activity were pre-test and post-test instruments. The data analysis technique used statistical analysis, namely the Wilcoxon test (P<0.05). The results of this service showed that students' knowledge and skills have increased in processing coffee into soap. In addition, students' understanding of the importance of washing hands with soap increased. It could be seen from the significant increase (P<0.05) incorrect answers in students' pre-test and post-test scores.